The Application of Saddhã to Astrologers’ Forecast - Thinakorn, Jindamard (วารสารสันติศึกษาปริทรรศน์ มจร, 2017)
This thesis, a qualitative-field research form done by the tools of documentary study and an in-depth interview with 9 key informants, is of 3 objectives: (1) to study Saddhã in Theravada Buddhism, (2) to study the role of astrologers, and (3) to analyze the role of astrologers towards the application of Saddhã for enhancing a peaceful life. From the research, it is found the followings: The conceptual idea of Saddhã in Buddhism is reasonable belief with wisdom by the confidence in the law of Kamma and its outcome; worldly humans and animal beings surely have one’s own Kamma and the wisdom of the Buddha’s Self-enlightenment. The role of astrologers is reading the map of fate or forecasting the fate in the past, present and future that things might happen to people and the society by means of reading the stars that show the various outcome of humans’ Kamma as the factor in forecasting. Thai Astrology is a subject originated from Phra Veddhaya Scripture in Brahmanism existed before Buddhism. 3) In analyzing the role of astrologers towards the application of Saddhã for enhancing a peaceful life from the conceptual idea of strengthening peace in Buddhism, the word “Peace” means the peaceful calmness which every human can possess.